Assistance in Understanding Digitalization Ethics for Students through Instilling Cultural Values - Zubaidah Zubaidah; Lusi Handayani; Winda Serly Utami; Nur Hasanah Harahap; Muhammad Alridho Lubis (Jurnal Masyarakat Religius dan Berwawasan, 2024)
Digitalization has a very broad influence on human life, one of which is the internet as a form of mass communication and the widespread use of the internet has an impact on human life, especially juveniles. Therefore, appropriate ethics are needed in its use. The aim of this trial is to provide assistance in increasing understanding of ethics in digitalization for students in the Guidance and Counseling Study Program. This service is carried out through 4 stages, namely; the foundation laying or building foundation phase, the research planning phase, the data collection and analysis phase, and the follow-up phase on research results. The result of this service is that students can increase their understanding of digitalization ethics. Based on these results, it can be concluded that one way to increase students' understanding of ethics in digitalization is by providing appropriate assistance, namely by integrating cultural values into its implementation. So it can be recommended for future researchers to continue the results of this service in the form of providing actions or interventions that can be practiced directly by students.